Biodegradation characteristics of duabanga moluccana blume and endospermum diadenum (Miq.) airy shaw - Hafizah, Abdul Razak. (Universiti Malaysia Sarawak (UNIMAS), 2005)
Biodegradation characteristics of fast growing pioneer wood species in Malaysia are still unknown due to lack of studies on them. The purpose of this study was to determine the biodegradation characteristics of some Sarawak pioneer wood species based on weight loss through two major tests, which are the modified ASTM soil block test and Termite Resistance Test. Two fast growing pioneer species were selected namely, Duabanga moluccana, Endospermum diadenum and Hevea brasiliensis used as control. For soil block test, the blocks were cut into cubes of 20mm. The cubes were exposed to two test fungi namely, Pycnoporus coccineus and Schizophyllllm commune, for eight week. Most of the wood weight loss exceed 10%, with Endospermum diadenum showed the highest weight loss among the two pioneer species, 19.64% for Pycnoporus coccineus and 7.06% for Schizophyllum commune, while Duabanga moluccana with 17.78% for Pycnoporus coccineus and 5.08% with Schizophyllum commune, the least between the three species. The termite resistance test was conducted according to JWPA standard and evaluated in a 3 week, no-choice laboratory tests. Cubes of 10mm x tOmm x 20mm were exposed to Coptotermes spp. of 150 workers and 50 soldiers in an acrylic cylinder. Duabanga moluccana is the most susceptible to termite attack among the two pioneer wood species with the highest weight loss at 6.33% and Endospermum diadenum , 4.11 %, the least susceptible among the wood species. This study showed that the fast growing pioneer species wood of Duabanga moluccana and Endospermlll1l diadenum are non-durable timber.